Correlation between mismatch repair statuses and the prognosis of stage I–IV colorectal cancer - Tong, Guojun; Zhang, Guiyang; Hu, Yan; Xu, Xuting; Wang, Yanyan (Frontiers in Oncology, 2024)
Background The role of microsatellite instability (MSI) and prognosis for stage II–III colorectal cancer (CRC) has been described, but the role of MSI in stage I and IV CRC is controversial. Methods A total of 2,540 CRC patients were collected from Huzhou Central Hospital, China, from January 2006 to 2016, and 783 cases were excluded. This retrospective study illustrates the correlation between MMR status and prognosis for 1,757 CRC patients as well as the correlation between MSI and prognosis for CRC patients. Two groups were classified as MSI-H and MSI-L&MSS. If the expression of one or more mismatch repair (MMR) proteins was negative, it was considered as microsatellite instability high expression (MSI-H), whereas positive expression was considered as microsatellite instability low expression and microsatellite stability (MSI-L&MSS), as assessed by correlation analyses. Overall and disease-free survival were analyzed using the Kaplan–Meier method. Univariable and multivariable analyses were conducted using Cox regression. Results Preoperative serum S-CEA, positive lymph, tumor size, pathologic tumor (Pt) status, node (N) stage, differentiation, chemotherapy, and the 8th Edition of the American Joint Committee on Cancer (AJCC-8) were significantly correlated with MSI (P=0.028, 0.037, 0.019, 0.007, 0.002, <0.001, <0.001, and <0.001, respectively), whereas tumor location was not associated with MSI. Univariable and multivariable analyses showed that MSI was an independent factor for CRC. The 5-year overall survival (OS) and 5-year disease-free survival (DFS, P<0.001) rates differed significantly between the two groups in stages II, III, and IV, whereas stage I did not show a significant difference (P>0.05). Conclusion MSI-H was associated with a good prognosis for stages II to IV, whereas stage I did not show any significant correlation. Moreover, MSI expression was an independent prognostic factor.